Star Wars : Mace Windu : the glass abyss - Barnes, Steven (Star wars., 2024)
"The Jedi are reeling from Qui-Gon Jinn's sudden death at the hands of a Sith. Jedi Master Mace Windu's feelings about Qui-Gon have always been complicated--and have not been made any simpler by death. While they often disagreed, Mace valued Qui-Gon's unique perspective, and their shared dedication to the Force made them allies. Without Qui-Gon and his unorthodox views, Mace feels out of balance. While considering his fallen friend's legacy, Mace is surprised to receive a final message from Qui-Gon, marked to be delivered to Mace in the event of Qui-Gon's death. The message contains a last request: a plea to help the Outer Rim planet Metagos. Many years ago, a violent solar flare transformed the surface of the desert planet into a landscape of irradiated glass--as beautiful as it is dangerous. Now most of the surviving inhabitants live underground, where rival clans fight to control the planet's limited resources. As a young Jedi, Qui-Gon protected the Sa'ad farming clan from the planet's less-scrupulous factions. The Sa'ad practice the art of dream-weaving, retaining their waking minds upon sleep in order to communicate and coexist with the wild creatures around them. Qui-Gon vowed to return if they ever required his aid, but now it falls to Mace to fulfill that promise. The Sa'ad's leader, KinShan Nightbird, has begged for the Jedi's help in freeing Metagos from the crime lords who threaten to eradicate her people's way of life. Intent on carrying out Qui-Gon's final wishes, Mace travels to Metagos and infiltrates the enemies of the Sa'ad. But as the Jedi Master investigates the intricate web of adversaries and allies, Mace finds himself pushed to the boundaries of the Jedi code, with his beliefs and his relationship to the Force itself challenged." --